ChemInform Abstract: Photoredox Mediated Nickel Catalyzed Cross‐Coupling of Thiols with Aryl and Heteroaryl Iodides via Thiyl Radicals. Issue 31 (14th July 2016) - Oderinde, Martins S.; Frenette, Mathieu; Robbins, Daniel W.; Aquila, Brian; Johannes, Jeffrey W.
Abstract: Highly chemoselective photoinduced Ni‐catalyzed cross‐coupling reactions of aryl, benzyl, and alkyl thiols with aryl and heteroaryl iodides in the presence of an Ir(III)‐photoredox catalyst are developed.